Conservation of Ancient Genetic Pathways for Intracellular Persistence Among Animal Pathogenic Bordetellae - Rivera, Israel; Linz, Bodo; Dewan, Kalyan K.; Ma, Longhuan; Rice, Christopher A.; Kyle, Dennis E.; Harvill, Eric T. (Frontiers in Microbiology, 2019)
Animal and human pathogens of the genus Bordetella are not commonly considered to be intracellular pathogens, although members of the closely related classical bordetellae are known to enter and persist within macrophages in vitro and have anecdotally been reported to be intracellular in clinical samples. B. bronchiseptica, the species closest to the ancestral lineage of the classical bordetellae, infects a wide range of mammals but is known to have an alternate life cycle, persisting, replicating and disseminating with amoeba. These observations give rise to the hypothesis that the ability for intracellular survival has an ancestral origin and is common among animal-pathogenic and environmental Bordetella species. Here we analyzed the survival of B. bronchiseptica and defined its transcriptional response to internalization by murine macrophage-like cell line RAW 264.7. Although the majority of the bacteria were killed and digested by the macrophages, a consistent fraction survived and persisted inside the phagocytes. Internalization prompted the activation of a prominent stress response characterized by upregulation of genes involved in DNA repair, oxidative stress response, pH homeostasis, chaperone functions, and activation of specific metabolic pathways. Cross species genome comparisons revealed that most of these upregulated genes are highly conserved among both the classical and non-classical Bordetella species. The diverse Bordetella species also shared the ability to survive inside RAW 264.7 cells, with the single exception being the bird pathogen B. avium, which has lost several of those genes. Knock-out mutations in genes expressed intracellularly resulted in decreased persistence inside the phagocytic cells, emphasizing the importance of these genes in this environment. These data show that the ability to persist inside macrophage-like RAW 264.7 cells is shared among nearly all Bordetella species, suggesting that resisting phagocytes may be an ancient mechanism that precedes speciation in the genus and may have facilitated the adaptation of Bordetella species from environmental bacteria to mammalian respiratory pathogens.